Local Culture-Based Literacy Instruction and Its Impact on Students’ Critical Reading Skills in Eastern Indonesia - Sangaji, Chairun M.; Ashar, Ibnu Khairul; Syah, Intan Kirani (Jurnal Tahuri, 2023)
This study explores how local culture-based literacy instruction enhances students’ critical reading skills in English as a Foreign Language (EFL) classrooms in three secondary schools in Ternate, Eastern Indonesia—SMAN 5 Ternate, SMAN 8 Ternate, and MAN 1 Ternate. The research addresses the dominance of conventional, text-centered literacy practices that confine learners to literal comprehension and hinder interpretive engagement. Drawing on Ternate’s oral traditions, royal histories, and maritime folklore, the study examines how integrating local narratives into reading activities promotes deeper, culturally grounded literacy. Using a qualitative multiple-case design, data were collected through classroom observations, interviews, and analysis of students’ reading journals. Thematic analysis combined critical literacy theory with sociocultural literacy perspectives to capture how learners negotiated meaning. Findings reveal that embedding local cultural content fosters inferential thinking, contextual understanding, and critical reflection, while increasing motivation and dialogic participation. However, constraints such as teachers’ limited capacity for culturally responsive pedagogy and the pressure of standardized assessments remain. The study’s novelty lies in formulating the Culturally Situated Critical Reading Framework, positioning reading as a socially mediated act linking identity, culture, and cognition. The research contributes to advancing critical literacy pedagogy, promoting culturally relevant language education, and expanding sociocultural perspectives in literacy studies.